Implementation of Village Fund Assistance in Village Development and Progress in Lebak Regency - Dede Ruky Racmat Racmat (International Journal of Social Sciences Review, 2023)
With the issuance of Law no. 6 of 2014, where villages can manage their own village administration, where village autonomy has consequences for the implementation of governance and village development based on good financial management, for the sake of increasing the welfare of village communities. The Village Fund is part of the Central Financial Balance fund, the rationale is in line with the Regional Autonomy agenda, where the use of Village Funds is very relevant to the perspective that places the village as a development benchmark, in early April 2019, the world experienced a difficult time with the emergence of the Covid-19 Pandemic which changed governance, socio-cultural and economic order. So on humanitarian grounds it was determined as a very extraordinary event, so that the use of Village Funds was prioritized for the provision of Bantuan Langsung Tunai (BLT) even though there were still many problems in its management. Researchers use the theory of qualitative methods with a contemporary qualitative analysis approach, namely Critical Systemic Thinking by considering the socio-political complexities that occur in the general public, according to Riswanda (2016) in relation to policy research methods, the gradation of complexity of social problems requires contemporary qualitative analysis where policy analysts are required to examine a social problem, the origins of a policy problem, using a multi-lens viewpoint accompanied by creativity in combining more than one variant of the approach in the policy research domain.